Huevos duros - Nunez, Marisa; Lima, Teresa (Pontevedra : OQO Editora, 2007)
A young king, who loves riddles and puzzles, becomes entranced with a peasant girl who possesses a knack for mind games. Based on a traditional story.
Series title appears as a stick figure drawing.
Keywords: Riddles, Juvenile; Kings and rulers -- Juvenile fiction; Peasants -- Juvenile fiction; Acertijos juveniles; Reyes y soberanos -- Novela juvenil; Campesinos -- Novela juvenil